Modeling and Simulation Analysis on Mixing Characteristics of Two-Phase Flow Around Spacer Grid - Xiao, Y.; Duan, T. C.; Ren, Quan-Yao; Zheng, Xiao-Yu; Zheng, Meiyin; He, Rui (Frontiers in Energy Research, 2022)
The spacer grid has a significant impact on the thermal-hydraulic characteristics of the rod bundle channel, which directly determines the possibility of a boiling crisis. The multi-phase flow model coupling boiling model is proposed to acquire the secondary flow and void fraction for subcooled flow boiling in the fuel assembly. Compared with the experimental data, the RNG k–ε turbulence model is selected in the current research. In addition, the thermal-hydraulic parameters of subcooled boiling flow in the 5 × 5 rod bundle with a spacer grid are studied focusing on the influence of different arrangements of mixing vanes. It is found that the distribution of the vapor phase is greatly influenced by the intensity and flow direction of secondary flow. In addition, the thermal–hydraulic characteristics in the sub-channels and around the fuel rods are investigated, which demonstrates that uniform crossflow makes vapor harder to accumulate around the fuel rods. Furthermore, the mixing characteristics of different types of spacer grids are also discussed in detail.